A protocol for identifying the needs related to drug use, health and social (re)integration of people living in prison within five European countries - Els Plettinckx; Nadine Berndt; Rita Seixas; Stefaan De Smet; Jérôme Antoine; Helena Bruggeman; Nina Harth; Athanasia Papadopoulou; Ioulia Bafi; Anastasios Fotiou; Evelina Pridotkienė; Rima Kalinauskaitė; et al. (BMC, 2024)
Abstract Background Compared to the general population, people living in prison are at an increased risk to experience negative (mental) health outcomes. Moreover, delinquency and drug use have many risk factors in common. A need exists for increasing the knowledge about health needs, drug use patterns and the coverage of drug-related interventions in prison within Europe. The current protocol describes the design of a study about wellbeing, drug use and related care in prison. Methods/design A multicentre mixed method design is implemented in five European countries (Belgium, Cyprus, Greece, Lithuania and Luxembourg). Qualitative and quantitative data collection tools are combined in order to generate complementary and comprehensive results. First, a cross-sectional survey among people living in prison is conducted. This survey is based on a model questionnaire, the European Questionnaire on Drug use among people living in Prison, developed by the European Monitoring Centre for Drug and Drugs Addiction. Second, people living in prison and people who have been recently released from prison are involved in qualitative semi-structured face-to-face interviews. The main topics of interest are the use of drugs and other health related topics such as loneliness, anxiety, depression, infectious diseases, suicide and treatment. Third, data regarding health and social reintegration measures in prison is collected through a quantitative survey addressed to the prison authorities. Discussion This study protocol presentes a European study which aims to assess drug use among people living in prison and recently released people who use drugs as well as the existing care services in prisons. Hereby, factors related to the prison environment and their needs, both inside and outside prison are taken into account. Importantly, this study protocol describes a methodology which is developed to be executed in different prison settings within different countries simultaneously. Accordingly, for each country the protocol is adjustable to specific national legal requirements, regional differences and distinct local regulations of prison administrations. However, extensive modularity inevitably comes with significant limitations of comparability and generalizability of the results.